The influence of political economy on nurses' post-registration development in the English NHS - Fisher, Nicola Mercedes (2025)
Registered nurses are the largest safety-critical profession in healthcare, and their post-registration development is essential for staff retention and high-quality patient care and safety. Despite this, nurses’ post-registration is limited, fragmented, and lacking in transparency. With an increasing national drive and focus in policy on enhancing patient care, safety, quality, and staff retention, exploring why nurses’ post-registration development is underdeveloped is essential for securing the future prospects of the health service. This thesis is grounded in the sociology of the professions, focusing on considering nurses' market shelter strengthening through the lens of political economy. The theoretical core of this PhD uses Light’s (1991, 1995, 2010) countervailing powers framework to consider the relationship between the state and the nursing profession. Consequently, the research question was: ‘Why has nursing in England not established a stronger market shelter through post-registration development and career frameworks, despite post-Fordist reforms?’. To enable the exploration of the research question, a qualitative research project was utilised, using a multi-method, multi-level research design incorporating NHS policy document analysis (n49) from 1989-2020, followed by semi-structured interviews over three levels. Macro (n9): individuals in national-level organisations that are influenced by or influence policy. Meso (n11): organisational leads, such as Chief Nurses. Micro (n27): registered nurses working in education, management, research and clinical areas. The findings are presented in a chapter for each level of analysis. The policy document analysis highlights the role of clinical governance and the ‘Agenda for Change’ NHS workforce policy, workforce planning and data and the instability of healthcare governance and policy. The macro analysis considers the challenges with Agenda for Change, data and government, and the short termism and instability of politics and policy. The meso analysis considers the role of organisational governance, networks and partnership working and clinical governance and data. Finally, the micro analysis considers training and development as a ‘luxury’ item, the role of middle management and the overall impact of the lack of post-registration development on nurses. The research question is answered through three core themes from the overall analysis, which are threaded throughout the different levels: first, the instability of healthcare policy; second, the lack of appropriate data and economic analysis; and finally, the juridification of practice. The overall implication from the analysis frames nurses’ post-registration development as a ‘wicked problem’. The potential future research from this thesis includes exploring the view of healthcare as a safety-critical industry and implications for workforce development, system-wide considerations of labour economics and workforce planning, and finally the ‘situated wickedness’ of clinical governance in relation to nursing workforce policy and management. Theoretically, this thesis provides an enhanced consideration of the state-profession relationship, including state actors and multi-level and multi-centric governance. Furthermore, it provides insight into the importance of stability in state projects, a focus on the economic within the ‘market’ and the increasing role of state-mandated legal mechanisms on professional practice. Critically, this PhD provides the development of a greater practice-theory perspective on professional development. Conceptually, this PhD indicates the importance and the role of workforce planning in relation to workforce development. Furthermore, how the healthcare industry is viewed as service or safety is explicitly linked to workforce development. Adjoining this is a greater emphasis on the role of data and economics, including how data is used to help a profession negotiate with various levels of power within a system.